Bronze Age Hill Forts: New evidence for defensive sites in the western Tian Shan, China. (September 2018) - Jia, Peter Weiming; Betts, Alison; Doumani Dupuy, Paula N.; Cong, Dexin; Jia, Xiaobing
Abstract : This paper reports on the recent discovery in western Xinjiang of three Late Bronze Age walled sites located on high hilltops, with a fourth on a terrace above a river bed. The hilltop sites contain very small clusters of residential structures and overlook one of the richest areas of seasonal pasture in the upper Bortala Valley, in the western Tian Shan. The walls do not fully encircle the residential structures but protect the most vulnerable points of access to the hilltops, and in particular protect against direct access from the pastures. The discovery of these walled sites in the western Tian Shan is surprising and significant in terms of regional patterns of increased social complexity in the Eurasian Late Bronze Age. It is suggested that the walled hilltop sites were lookout posts, with a small garrison of herders prepared to defend the area in the event of attack by rival pastoralist groups, and that in the Late Bronze Age the Upper Bortala Valley was home to a number of pastoralist groups who contested access to the best pastures.